Peningkatan Kemampuan Berpikir Kritis Anak Usia Dini Melalui Model Pembelajaran Berbasis Proyek - Irma Yuliantina; Venty Indah Puspitasari (Universitas Islam Lamongan, 2025)
One of the important competencies that must be possessed by children in the 21st century is the ability to think critically. This study aims to find the right method for early childhood in improving critical thinking skills. Project-based learning is predicted to improve children's thinking skills in a fun and meaningful way according to learning in early childhood. This research method uses a descriptive qualitative approach. The results showed that project-based learning is directly proportional to critical thinking skills. High questioning ability with a percentage of 95.65% is directly proportional to projects focused on questions or problems with a percentage of 94.90%. Similarly, low analytical skills with a large percentage of 79.23% are directly proportional to projects that have development stages where children can solve problems with a large percentage of 79.00%. Project-based learning methods are proven to improve children's critical thinking skills by involving children in the learning process optimally.